Effect of Postoperative Repair Integrity on Health-Related Quality of Life After Rotator Cuff Repair: Healed Versus Retear Group. (November 2013) - Yoo, Jae Hyun; Cho, Nam Su; Rhee, Yong Girl
Background: Although rotator cuff repair is performed to improve health-related quality of life (HRQL) by reducing pain and improving shoulder function, it has not been clearly demonstrated that HRQL is improved in retear cases. Purpose: To compare HRQL outcomes after rotator cuff repair between patients with healed cuffs and those with retears using the Short Form–36 Health Survey (SF-36). Study Design: Cohort study; Level of evidence, 3. Methods: A total of 81 patients who underwent rotator cuff repair were enrolled in this study. There were 56 patients in the healed group and 25 patients in the retear group. The mean age at the time of surgery was 56 years (range, 35-73 years) in the healed group and 59.7 years (range, 45-74 years) in the retear group. The mean follow-up period was 29.7 months (range, 14-95 months) and 26.4 months (range, 13-101 months) in the healed and retear groups, respectively. Results: At final follow-up, the SF-36 scores for physical and mental component summaries (PCS and MCS, respectively) revealed significant improvement, from 36.6 to 51.2 (PCS) and 34.4 to 51.6 (MCS) in the healed group ( P < .0001 in both cases) and from 34.2 to 49.4 (PCS) and 33.4 to 53.2 (MCS) in the retear group ( P < .0001 in both cases). Mean scores on the SF-36 subscale for role limitations because of physical health problems (RP) were 52.3 in the healed group and 50.6 in the retear group. The RP and PCS scores were significantly higher in the healed group ( P = .007 and P = .025, respectively). All domains and component summaries also had a fair to moderate correlation (range, 0.296-0.496) with the SF-36 score. Conclusion: Although clinical shoulder outcome measures (University of California, Los Angeles [UCLA] and American Shoulder and Elbow Surgeons [ASES] scores) and all dimensions of the SF-36 showed significant improvement in both groups after rotator cuff repair, scores were significantly higher in the healed group on RP and PCS of the SF-36 as well as on the UCLA and ASES. There was no significant difference in MCS scores between the 2 groups. Despite similar improvements in the MCS scores, there were apparent objective differences between the groups. The values were statistically significant but clinically not significant for some of these measures.